FLOUR CHARACTERISTIC FROM FISH WASTE IN FORM OF GOURAMY (Osphronemus Gouramy) SCALES, SKINS AND CATFISH (Pangasius Hypopthalmus) BONES AS INDUSTRY MAIN INGREDIENTS - Raja Alvano Putra; Syahrul '; Dewita Buchari (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2016)
This research aims to understand flour characteristic from solid waste of gouramy and catfish processing ( scales, skins, and bones ). This research used experiment method, with 4% NaoH submersion during 2 hours and 80O C extraction temperature. the analized parameter was water content, ash content, protein content, pH, and Cu metal content on fish waste which were scales, skins, and bones. Fish scales and fish bones extraction result were relatively better than skins flour. Result from analyzed for scales had 28, 43% rendement, 2,81% water content, 71,67% Ash content, 2,62% Cu metal content, and 7,53 pH. Meanwhile for bones flour had 6,11% rendement, 3,06% water content, 66,34% Ash content, 6,80% Cu metal content, and 7,20 pH, and skins had 15,73% rendement, 7,69% water content, 62,03% ash content, 5,51% Cu metal content, and 7,90 pH.Keywords: Gouramy Fish, Catfish, Skins, Scales, Flour, Bones.